(untitled) (Journal of Parents and Teachers, 2014)
The fever of blogs has entered with force in the educational world. Due to the ease of creation and writing in them and their versatility, many teachers have decided to use them as a didactic resource in their classes. The article explains its benefits and outlines the steps and guidelines to follow to create our own.